A simple mathematical study of anterior dental relations Part III: incisor and canine overbite - Cordato Mark A. (Sciendo, 1998)
Two previous articles described horizontal interarch relations with a simple model developed. This paper required further development of the horizontal relations to al low vertical overlap to be studied. An analysis of orthodontic and dental-prosthetic models provided values to refine horizontal description then guide vertical calculations. Tooth thickness and angles of the maxiIlary teeth were related to horizontal overlap to produce an estimate of potential overbite. Principles were derived from the calculations and stated. Change can be predicted for overjet and overbite during and after orthodontic treatment. This series of articles expands the logical foundations by rationally considering a broad range of anterior occlusions. There are limitations in observing one or two features of anterior occlusion without comprehending the influence of other significant measurements. Measuring change in anterior overbite is inadequate without concurrently accounting for changes of other variables such as: spacing/enlarging/hypodontia; crowding; buccal relations and tooth thickness. A better understanding of anterior dental relations is possible from use of this model and the principles derived from it.